Genetic Differentiation and Demographic Trajectory of the Insular Formosan and Orii's Flying Foxes. (1st March 2021) - Lin, Kung-Ping; Chaw, Shu-Miaw; Lo, Yun-Hwa; Kinjo, Teruo; Tung, Chien-Yi; Cheng, Hsi-Chi; Liu, Quintin; Satta, Yoko; Izawa, Masako; Chen, Shiang-Fan; Ko, Wen-Ya
Abstract: Insular flying foxes are keystone species in island ecosystems due to their critical roles in plant pollination and seed dispersal. These species are vulnerable to population decline because of their small populations and low reproductive rates. The Formosan flying fox ( Pteropus dasymallus formosus ) is one of the 5 subspecies of the Ryukyu flying fox. Pteropus dasymallus formosus has suffered from a severe decline and is currently recognized as a critically endangered population in Taiwan. On the contrary, the Orii's flying fox ( Pteropus dasymallus inopinatus ) is a relatively stable population inhabiting Okinawa Island. Here, we applied a genomic approach called double digest restriction-site associated DNA sequencing to study these 2 subspecies for a total of 7 individuals. We detected significant genetic structure between the 2 populations. Despite their contrasting contemporary population sizes, both populations harbor very low degrees of genetic diversity. We further inferred their demographic history based on the joint folded site frequency spectrum and revealed that both P. d. formosus and P. d. inopinatus had maintained small population sizes for a long period of time after their divergence. Recently, these populations experienced distinct trajectories of demographic changes. While P. d. formosus suffered from a drastic 10-fold population decline not long ago, P. d. inopinatus underwent a 4.5-fold population expansion. Our results suggest separate conservation management for the 2 populations—population recovery is urgently needed for P. d. formosus while long-term monitoring for adverse genetic effects should be considered for P. d. inopinatus .